How can integrated morphotaxonomy-and metabarcoding-based diatom assemblage analyses best contribute to the ecological assessment of streams? - Pissaridou, Panayiota; Cantonati, Marco; Bouchez, Agnès; Tziortzis, Iakovos; Dörflinger, Gerald; Vasquez Christodoulou, Marlen (My University, 2021)
Environmental conditions, such as nutrient concentrations, salinity, elevation etc., shape diatom assemblages of periphytic biofilms. These assemblages respond rapidly to environmental changes, a fact which makes diatoms valuable bioindicators. Hence, freshwater biomonitoring programmes currently use diatom indices (e.g. EU Water Framework Directive - WFD). To date, microscopy-based assessments require high taxonomic expertise for diatom identification at the species level. High-throughput technologies now provide cost-effective identification approaches that are promising, complementary or alternative tools for bioassessment. The suitability of the metabarcoding method is evaluated for the first time in the Cyprus streams WFD monitoring network, an eastern Mediterranean country with many endemic species and results are compared to the results acquired from the morphotaxonomic analysis. Morphotaxonomic identification was conducted microscopically, using the most updated taxonomic concepts, literature and online resources. At the same time, DNA metabarcoding involved the use of the rbcL 312 bp barcode, high-throughput sequencing and bioinformatic analysis. The ecological status was calculated using the IPS Index. Results show a positive correlation between morpho-taxonomic and molecular IPS scores. Discrepancies between the two methodologies are related to the limitations of both techniques. This study confirmed that Fistulifera saprophila can have a crucial role in key differences observed, as it negatively influences IPS scores and microscopy methods frequently overlook it. Importantly, gaps in the DNA barcoding reference databases lead to a positive overestimation in IPS scores. Overall, we conclude that DNA metabarcoding offsets the morphotaxonomic methodology for the ecological quality assessment of freshwaters.
Keywords: DNA metabarcoding; Morpho-taxonomy; River biomonitoring; Cyprus rivers